Plexual cholesteatosis in horses. A study of twenty eight cases - Santos, Jefferson Andrade dos; Carvalho, Eulógio Carlos de Queiroz; Cony, Carlos Alberto de Oliveira; Muchaluat, Marco Antonio (Pesquisa Agropecuaria Brasileira, 2014)
The authors realized a sequence of studies about plexual cholesteatosis in horses, concerning various aspects of this disease. Clinically, the animals definitelly showed phenomena of motor origin. One of the horses presented blood leucocytosis and striking liquor pleocytosis. The affection was present in 28% of a lot of 25 horses, 21 of whom being more than ten years old. The authors observed that the disease affected only the lateral ventricles, and the lesions were either multiple and numerous or scarce and voluminous. Histologically the lesions demonstrated calcification in 50% of the cases and hemosiderophages infiltration in 38%. The Schultz reaction for histochemically characterization of cholesterol proved to be positive. The thin layer chromatography on silica gel proved that the crystals present in the lesions were constitued by cerebronic acid and cholesterol lignocerat.